Raw data on acceptance and emergence in intrinsic competition experiments, and guarding behavior in extrinsic competition: Trissolcus cultratus and Trissolcus japonicus - Gariepy, Tara (Dryad, 2021)
Understanding competition between scelionid parasitoids that exploit the
same host may provide insight into strategies that allow co-existence on a
shared resource. Competition studies typically focus on interactions
between native and exotic parasitoids that do not share an evolutionary
history; however, co-evolved parasitoids may be more likely to demonstrate
strategies to avoid or exploit a shared resource. We examined intrinsic
and extrinsic competition between Asian Trissolcus japonicus Ashmead and
T. cultratus Mayr (Hymenoptera: Scelionidae) associated with Halyomorpha
halys Stål (Hemiptera: Pentatomidae) that share an evolutionary history.
Interspecific interactions were assessed by providing parasitized egg
masses to each species at various intervals post-parasitism, and measuring
host acceptance, developmental suitability, and guarding behaviour.
Trissolcus japonicus showed high acceptance of parasitized hosts up to 72h
following oviposition by T. cultratus, despite a very poor developmental
outcome. In contrast, T. cultratus generally avoided ovipositing in H.
halys eggs containing T. japonicus early-instar larvae, but did not avoid
parasitizing H. halys that contained eggs and third instar larvae. The
adaptive value of this behaviour was supported by developmental outcome:
T. cultratus outcompeted T. japonicus eggs but not early-instar larvae,
and a trophic shift occurred wherein T. cultratus developed as a
facultative hyperparasitoid on third instar T. japonicus larvae.
Trissolcus japonicus guarded egg masses 8 – 12x longer and displayed more
aggressive interactions than T. cultratus, suggesting T. japonicus is the
superior extrinsic competitor. Development as a facultative
hyperparasitoid provided a competitive niche for Asian T. cultratus and
confirms its instrinsic competitive superiority. This also occurs in a
biologically-distinct European population of T. cultratus, suggesting that
facultative hyperparasitism as a competitive strategy is retained in
geographically-separated populations that have not co-evolved with H.
halys or T. japonicus.
Extrinsic competition (Associated with file 05.
Extrinsic Competition Behavior Data.csv) Individual, 4 days old females of
T. japonicus (TJ) and T. cultratus (TC) were provided
individually with single H. halys egg masses of regular size (28 eggs) in
small plastic dishes (5 x 1 cm). Females were observed under the
stereomicroscope until they parasitized all eggs and initiated brood
guarding behaviour. Single females of the second species were then added
to each dish through a small resealable hole on the side. Interactions of
competing females were filmed for 30 min with a portable digital
microscope and analysed with Observer XT software (Noldus Information
Technology B.V., The Netherlands). Replicates in which wasps showed no
interest in the egg mass (no searching behaviour, no interaction with the
competitor) were excluded from the analysis.For the guarding wasps (1st)
the following parameters were recorded: guarding the egg mass, patrolling
on the leaf, chasing competing wasp, fighting (direct physical contact
with competitor) and walking off the leaf. For the competitor (2nd
species) added to the petri dish containing a guarding wasp, seven
behavioural categories were defined: walking off the leaf, walking on the
leaf, drumming on the egg mass, ovipositing, marking parasitized eggs,
chasing guarding wasp and fighting. For both wasp species the last two
categories were considered as aggressive behaviour towards the competitor.
When the competing wasp was able to complete oviposition (indicated by
marking) on at least one of the guarded eggs, extrinsic competition was
considered successful. The following abbreviations are used in the table:
Observations.    Replicates W_Guard.
Wasp species guarding
W_Compet        Wasp
species competing Tguard
Time spent guarding
by the guarding wasp Tempty_GW
Time spent in the empty space by the guarding wasp
Tleaf_GW
Time spent on the leaf by the guarding wasp
Tfight_GW         Time spent
fighting by the guarding wasp Tempty_CW.
Time spent in the empty space by the
competing wasp Tleaf_CW
Time spent on the leaf by
the competing wasp Tdrum
Time
spent drumming (logically by
the competing wasp) TOvip

Time
spent ovipositing (logically by
the competing wasp) TMark

Time spent marking (logically by
the competing wasp) Tfight_CW
Time
spent competing by the competing wasp
Nguard
Number of times guarding the egg mass within 30 min
(by the guarding wasp) Nempty_GW   Number of times spent
in the empty space (by the guarding wasp)
Nleaf_GW     Number of times spent on
the leaf within 30 min ( by the guarding wasp)
Nchase_GW   Number of times chasing the competitor
within 30min (by the guarding wasp)
Nfight_GW     Number of
times fighting with competing wasp within 30min (by
the guarding wasp ) Nempty_CW   Number
of times spent in the empty space within 30min (by the
competing wasp)
Nleaf_CW        Number of times on the leaf within 30 min (by the competing wasp) Nchase_CW     Number of times chasing the guarding wasp within 30min (by the competing wasp) Ndrum              Number of times drumming on the egg mass within 30min (by the competing wasp) Novip               Number of times ovipositing within 30min (by the competing wasp) Nmark              Number of times marking within 30min (by the competing wasp) Nfight_CW      Number of times fighting with guarding wasp within 30 min( by the competing wasp) Duration           Duration of the observation (30 minutes) Duration of guarding behaviour (Associated with file 01. Trissolcus japonicus Raw data host guarding experiment.csv and 02. Trissolcus cultratus Raw data host guarding experiment.csv) Females of each parasitoid species were exposed individually to fresh H. halys egg masses (28 eggs) in small Petri-dishes (5cm diameter) with a 5mm hole in the lid, which was closed with a piece of foam. Females were observed until they had parasitized all eggs and started to guard the parasitized egg mass. Once guarding was observed, each plastic dish containing a wasp was placed individually in a larger 1.2L plastic container, the foam stopper on the petri dish was removed, and the larger container was sealed to prevent escape. Wasps were monitored every hour to determine whether they continued to guard the egg mass (Guarding, G) or had left the egg mass and had entered the larger container, indicating that they were no longer guarding the egg mass (Off the egg mass, O). Acceptance of and emergence from multiparasitised host egg masses (Intrinsic competition) (Associated with file 03. acceptance and multiparasitism behavior.csv and 04. Emergence from multiparasitized eggs.csv) Assays were carried out in small plastic dishes (5 x 1 cm), and observations were made using a stereomicroscope, following the experimental design of Konopka et al. (2017). Randomly selected T. japonicus females (2-7 days old, mated, naïve) were offered fresh (< 24 h) H. halys egg masses (12 eggs/ mass) and observed until all eggs were parasitized, indicated by the characteristic marking behaviour. Trissolcus cultratus females (2-7 days old, mated, naïve) were provided egg masses previously parasitized by T. japonicus 0, 24, 48, 96, and 120h earlier (note that 0h refers to an egg mass that was parasitized by the first species, and then immediately offered to the second species), and observed until they parasitized the entire egg mass or until females left the egg mass for >10 min. This approach ensured that parasitoids were provided parasitized hosts at different stages of embryonic development [i.e., parasitoid egg (0h), larvae (24 – 72h), pre-pupae (96h) and pupae (120h); as per Volkoff & Colazza, 1992; Adidharma & Ciptadi, 2012; Konopka et al., 2020]. As controls, fresh H. halys egg masses (12 eggs/mass) were offered to T. cultratus and T. japonicus females separately to estimate emergence without competition. The number of eggs attempted (drilled) and parasitized (marked) by each T. cultratus female was recorded. Egg masses were kept for three weeks and all parasitoid adults obtained were identified to species based on morphological characteristics (Talamas et al., 2017). The same experiment was repeated in reverse order, providing eggs first to T. cultratus followed by T. japonicus.
Keywords: FOS: Biological sciences